A decade of action for a change of era (United Nations, ECLAC, 2022)
For the fifth time, the countries of the region are convening in the framework of the Forum of the Countries of Latin America and the Caribbean on Sustainable Development. On each occasion, the Economic Commission for Latin America and the Caribbean (ECLAC) has presented a report on regional progress and challenges in relation to the 2030 Agenda for Sustainable Development. Since 2020, efforts to assess progress towards meeting the 2030 Agenda have had to be undertaken amid the constraints imposed by measures to address the coronavirus disease (COVID-19) pandemic.In this difficult context, ECLAC continued to step up its efforts to assess the progress towards the achievement of the Sustainable Development Goals (SDGs). Whereas in 2019 we only had 19 statistical series of SDG indicators for the region to analyse progress towards 2030, in this fifth report we are presenting the results for 359 series, corresponding to 111 targets, 73 of which are targets covered by the prioritized indicators for the region.Given the contradiction between, on the one hand, the growing institutional efforts to bring to fruition the Decade of Action of the Sustainable Development Goals called for by the United Nations Secretary-General and his proposal of Our Common Agenda and, on the other, the insufficient progress towards the achievement of the Goals, ECLAC stresses once again its proposal to launch a decade of action for a change of era. The Sustainable Development Goals will not be achieved by doing more of the same; we must move towards a new, inclusive and sustainable economic and social system.This document presents specific proposals in four areas in which we must continue to work: strengthening multilateralism, particularly in the area of financing for development; improving implementation of productive, social and environmental policies of national and regional scope; building up the resilience of institutions; and overcoming conflicts through agreements and compacts. Foreword .– Chapter I. Asymmetries, the impact of the pandemic and the cost of not committing to the future. A. The economic impact of the pandemic has been stronger in Latin America and the Caribbean than in other regions of the world. B. Social impact amplified by the inequality matrix. C. Global warming and the environmental vulnerability of the region .– Chapter II. Trends in the Sustainable Development Goal indicators .– Chapter III. Progress on quality education, gender equality and marine and terrestrial ecosystems .– Chapter IV. Institutional progress on the means of implementation of the 2030 Agenda for Sustainable Development .– Chapter VAgreements for a decade of action. A. Multilateralism, international financing and regional integration. B. Public policy at the core of a transformative recovery. C. Governance in a new pattern of development. D. Conflicts, instability and social compacts for sustainable development.
11362/47746
Keywords: Graue Literatur; Amtliche Publikation; Konferenzschrift; financing for development; inclusive development; inequality; international trade; macroeconomics; public policies; sustainable development; 2030 Agenda for Sustainable Development; economic development; social development; viruses; epidemics; Sustainable Development Goals; education; gender equality; marine ecosystems; terrestrial ecosystems; international cooperation; civil society; multilateralism; development models; development finance; social policy; DESARROLLO ECONOMICO; DESARROLLO SOCIAL; DESARROLLO SOSTENIBLE; COVID-19; VIRUS; EPIDEMIAS; OBJETIVOS DE DESARROLLO SOSTENIBLE; EDUCACION; IGUALDAD DE GENERO; ECOSISTEMAS MARINOS; ECOSISTEMAS TERRESTRES; AGENDA 2030 PARA EL DESARROLLO SOSTENIBLE; COOPERACION INTERNACIONAL; SOCIEDAD CIVIL; MULTILATERALISMO; MODELOS DE DESARROLLO; FINANCIACION DEL DESARROLLO; POLITICA SOCIAL; ECONOMIC DEVELOPMENT; SOCIAL DEVELOPMENT; SUSTAINABLE DEVELOPMENT; VIRUSES; EPIDEMICS; SUSTAINABLE DEVELOPMENT GOALS; EDUCATION; GENDER EQUALITY; MARINE ECOSYSTEMS; TERRESTRIAL ECOSYSTEMS; 2030 AGENDA FOR SUSTAINABLE DEVELOPMENT; INTERNATIONAL COOPERATION; CIVIL SOCIETY; MULTILATERALISM; DEVELOPMENT MODELS; DEVELOPMENT FINANCE; SOCIAL POLICY